PERTANGGUNGJAWABAN PIDANA PEMBUAT KONTEN PERJUDIAN ONLINE BERBASIS LIVE STREAMING DITINJAU DARI KUHP DAN UU ITE - Khusnul Khotimah; Nadia Fransisca Sagala; Rimadhani Mardhotillah; Legita Assriyani (PT. Hasba Edukasi Mandiri, 2025)
This research aims to find out about live streaming-based online gambling content in criminal law and to find out the criminal liability of the perpetrators of live streaming-based online gambling content. This research method uses normative juridical research methods, with the research specifications used are the statutory approach, the news approach regarding online gambling and the case approach. The data source used is secondary data which consists of primary, secondary and tertiary legal materials, with literature study data collection techniques. The results of the research obtained are that online gambling content in criminal law is a criminal offense because it fulfills the elements of a criminal offense and there are regulations regarding gambling located in Articles 303 and 303bis of the Criminal Code, Article 426, Article 427 of Law No. 1 of 2023 and Article 27 paragraph (2) of the ITE Law. As for criminal liability regarding online gambling content creators, it is still arguably quite a few who can be held accountable.